Sistem Informasi Inventory Gudang Berbasis Desktop Pada PT Besmindotama Semesta - Nazwa Oktaviani Alemadi (ALMUISY: Journal of Al Muslim Information System, 2022)
Currently the development of information technology is growing rapidly and demands to create an application that can solve an existing problem but has not found a solution. In the process of knowing the amount of stock, sometimes it will be difficult if you have to check manually. This application at PT Besmindotama Semesta is based on the need for precise and accurate information management in managing the status of goods in the warehouse. The methodology used is the waterfall method, this model describes software development such as a waterfall flow, starting from requirements analysis as the beginning of the process to coding and testing at the end of the process. its manufacture. This information system is made using the Java programming language and MySQL as the database. The author uses data flow diagrams to design the workflow scheme of this system and ERD to create relationships between tables. The result of this research is to create a desktop-based inventory information system that can simplify inventory and speed up the process of delivering inventory information.